Applying of open gas generators in solid fuel for rising underwater objects; AIP Conference Proceedings; Vol. 2103 : Fundamental and applied problems of modern mechanics (FAPMM 2018) - Barsukov V. D. Vitaly Dimentjevich (2019, 2019)
Title screen